M145. ALTERED SUBCORTICAL EMOTIONAL SALIENCE PROCESSING AND A 'JUMPING TO CONCLUSIONS' BIAS IN PARKINSON'S PATIENTS WITH PSYCHOTIC SYMPTOMS. (18th May 2020) - Knolle, Franziska; Garofalo, Sara; Viviani, Roberto; Ermakova, Anna; Murray, Graham
Abstract: Background: Current research does not provide a clear explanation for why some patients with Parkinson's Disease (PD) develop psychotic symptoms. In schizophrenia research the 'aberrant salience hypothesis' of psychosis has been influential in explaining the development of psychotic symptoms. The theory proposes that dopaminergic dysregulation leads to inappropriate attribution of salience to otherwise irrelevant or non-informative stimuli, facilitating the formation of hallucinations and delusions, by providing irrational explanations. However, this theory has received very limited attention in the context of PD-psychosis. Methods: In the study, we investigated salience processing in 14 PD-patients with psychotic symptoms, 23 PD-patients without psychotic symptoms and 19 healthy controls. All patients received dopaminergic medication. There was no difference in the medication dose between the two patient groups. We examined emotional salience using a visual oddball fMRI paradigm that has been used to investigate early stages of schizophrenia spectrum psychosis, controlling for resting cerebral blood flow (arterial spin labelling fMRI). Furthermore, a subgroup of the two patient groups complete a behavioural 'jumping to conclusions' task. Results: We found significant differences in brain responses to emotional salience between the two patient groups. PD-patients with psychotic symptoms revealed enhanced brain responses in the striatum, the hippocampus and the amygdala compared to patients without psychotic symptoms. PD-patients with psychotic symptoms showed significant correlations between the levels of dopaminergic drugs they were taking and BOLD signalling, as well as psychotic symptom scores. Furthermore, our data provide first indications for dysfunctional top-down processes, measured in a 'jumping to conclusions' bias. Discussion: Our study suggests that enhanced signalling in the striatum, hippocampus and amygdala together with deficient top-down cognitive regulations is associated with the development of psychotic symptoms in PD, similarly to that proposed in the 'aberrant salience hypothesis' of psychosis in schizophrenia.